Social Difficulties As Risk and Maintaining Factors in Anorexia Nervosa: A Mixed-Method Investigation - Cardi, Valentina; Mallorqui-Bague, Núria; Albano, Gaia; Monteleone, Alessio Maria; Fernandez-Aranda, Fernando; Treasure, Janet (Frontiers in Psychiatry, 2018)
Anorexia nervosa is a serious psychiatric disorder characterised by severe restriction of energy intake and dangerously low body weight. Other domains of functioning are affected, including social functioning. Although difficulties within this domain have started to be acknowledged by the literature, some important gaps remain to be filled. Do social difficulties predate the onset of the illness? What difficulties in particular are relevant for the development and maintenance of the illness? The aim of this study is to combine the use of quantitative and qualitative methods to answer these questions. Ninety participants with lifetime anorexia nervosa (88 women and two men) completed an online survey assessing memories of involuntary submissiveness within the family, fear of negative evaluation from others, perceived lack of social competence, feelings of social belonging, eating disorder symptoms, and work and social adjustment. Participants also answered three open questions regarding their experience of social relationships before and after the illness onset. The findings provided support for the hypothesised relationships between the study variables. Involuntary submissiveness and fear of negative evaluation predicted eating disorder symptoms and these associations were partially mediated by perceived lack of social competence. Two thirds of the sample recalled early social difficulties before illness onset and recognised that these had played a role in the development of the illness. A larger proportion of participants stated that the eating disorder had affected their social relationships in a negative way. This study sheds some light on patients’ perspective on the predisposing and maintaining role that social difficulties play in anorexia nervosa and identifies key psychological variables that could be targeted in treatment.